Foreign Translators Group in the PRC From 1949 to 1966: A STP Perspective - Chen Longzhan (Open Cultural Studies)
Throughout the history of translation in China, almost every major translation movement has been accompanied by the activities of foreign translators. China, during the seventeen years from 1949 to 1966, absorbed a large number of foreign translators, who made significant contributions to the translation profession of the People’s Republic of China (PRC). These foreign translators participated in China’s translation practice, resulting in distinct characteristics of the translators group. This article takes the concept of the “translator community” of the State Translation Program (STP) as the departing point to explore the characteristics of the foreign translators group engaged in STP in China from 1949 to 1966 and digs out the reasons behind the generation of the foreign translators group. It is found that the foreign translators group in the early 17 years after the founding of the PRC are specifically manifested as the translator positioning of state translators, the predominant translator identity of non-professionals, and the translator image of “gears” and “repairmen.” The generation of these groups is the result of multiple factors, including the state’s strategic requirement for translation output, the state’s macro-regulation of the allocation of translation talent resources, as well as the state’s manipulation of the translation process.